2008
DOI: 10.1007/s00436-008-1014-4
|View full text |Cite
|
Sign up to set email alerts
|

Learning and orientation to odor in the bug Rhodnius prolixus Stal 1859 under laboratory conditions

Abstract: Two experiments are described investigating learning and orientation in the triatomine Rhodnius prolixus. In experiment 1, Pavlovian conditioning was investigated. The experiment differed from our previous work in that the intensity of the conditioned and unconditioned stimuli were reduced and the number of training trials increased. Once again, no evidence for Pavlovian conditioning was found. In experiment 2, an "orientation arena" was developed in which the orientation of R. prolixus to a human forearm was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Concerning R. prolixus, only negative results have been reported (Abramson et al, 2005;Aldana et al, 2008). In the present study, the accumulated knowledge on R. prolixus biology was exploited in order to adapt a conditioning procedure to its haematophagous way of life and to assess whether their behavioural response to a neutral odour could be modified by individual experience.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Concerning R. prolixus, only negative results have been reported (Abramson et al, 2005;Aldana et al, 2008). In the present study, the accumulated knowledge on R. prolixus biology was exploited in order to adapt a conditioning procedure to its haematophagous way of life and to assess whether their behavioural response to a neutral odour could be modified by individual experience.…”
Section: Discussionmentioning
confidence: 98%
“…Comparing our experimental approach to previous ones may shed some light on the reasons behind these contradictory results, and provide some insights for future work. In their foray, Abramson et al (Abramson et al, 2005) and Aldana et al (Aldana et al, 2008) also paired an olfactory CS with a thermal US using an artificial feeder. The major differences with our work lie in the way they developed their experimental design.…”
Section: Vinauger L Buratti and C R Lazzarimentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies, however, were unsuccessful in demonstrating the ability of the bugs to perform associative learning [23-24]. These negative results could have been due to the fact that the stimuli and reward did not adequately match the biology of bugs.…”
Section: Recent Advances In Vector Learning and Memorymentioning
confidence: 99%
“…Conditioning has been shown in R. prolixus [10], [11], D. melanogaster [12], and the parasitic wasp Microplitis croceipes [13]. For mosquitoes, some studies have found no evidence for behavioral adaptation [14], [15], while more recent work has demonstrated conditioning to odours [16]–[18].…”
Section: Introductionmentioning
confidence: 99%